Unveiling Species Diversity Within Early-Diverging Fungi from China VII: Seven New Species of Cunninghamella (Mucoromycota) - Zi-Ying Ding; Meng-Fei Tao; Xin-Yu Ji; Yang Jiang; Yi-Xin Wang; Wen-Xiu Liu; Shi Wang; Xiao-Yong Liu (Journal of Fungi)
The fungal genus Cunninghamella, ubiquitously distributed as saprotrophic organisms with occasional endophytic and phytopathogenic manifestations, holds significant biomedical and biochemical importance. During systematic investigations of fungal biodiversity in China, seven novel taxa (C. amphispora sp. nov., C. cinerea sp. nov., C. flava sp. nov., C. hainanensis sp. nov., C. rhizoidea sp. nov., C. simplex sp. nov., and C. yunnanensis sp. nov.) were delineated through integrated taxonomic approaches incorporating morphological characterization, multilocus phylogenetic analyses (ITS-LSU-TEF1α), and physiological assessments. Phylogenetic reconstructions positioned these novel species within a well-supported clade along with C. bainieri and C. verticillata. New species and their diagnostic features are C. amphispora, exhibiting dimorphic sporangiola production; C. cinerea, distinguished by gray pigmentation in the colony; C. flava, characterized by a yellow colony; C. hainanensis and C. yunnanensis, bearing eponymous designations reflecting their geographic origins; and C. simplex, displaying simplified sporangiophore branching. Comprehensive taxonomic descriptions accompanied by photomicrographic illustrations are provided herein. This study constitutes the seventh installment in an ongoing series elucidating early-diverging fungal diversity in China, expanding the global Cunninghamella taxonomic inventory to 63 species and advancing our understanding of mucoralean phylogeny.